Environmental risk factors for diarrhea Children under five years of age: A Cross-Sectional study in Indonesia - Santri, Ichtiarini Nurullita; Wardani, Yuniar (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: Diarrhea is an environmental-based disease that causes mortality and morbidity in children under five around the world. This study investigated the association between environmental factors with diarrhea in children under five in Indonesia. Methods: A cross-sectional study was conducted with data derived from the 2017 Indonesia Demographic Health Survey (IDHS). Families with children under five who had complete data were included in this study. The diarrhea variable in children was self-reported by their mothers. The relationship of each predictor with diarrhea was analyzed using a logistic regression modeling and odds ratios (ORs) with 95% confidence intervals (CI). Results: A total of 17,155 households with children under five were included. The prevalence of reported diarrhea among children under five was 14.22%. Families living in rural areas (OR: 0.87; 95%CI: 0.78-0.97) and mothers of 25-34 years of age (OR: 1.42; 95%CI: 1.24-1.64) and >35 years of age (OR: 1.56; 95%CI: 1.29-1.89) had significant associations with diarrhea. Conclusion: The discerned outcomes underscore the amplified likelihood of diarrhea incidents among children under five originating from rural residential settings in contrast to their urban counterparts. Additionally, the investigation underscored a correlative link between maternal age and occurrences of diarrhea in the children of this specific age group mothers.